Accessing alpha-arylated nitriles via BF3 center dot OEt2 catalyzed cyanation of para-quinone methides using tert-butyl isocyanide as a cyanide source - Shirsath, Sachin R.; Shinde, Ganesh H.; Shaikh, Aslam C.; Muthukrishnan, M. (Journal of Organic Chemistry, 2018)
BF3 center dot OEt2 catalyzed 1,6-conjugate addition of tertbutyl isocyanide to para-quinone methides and fuchsones for the synthesis of alpha-diaryl and alpha-triaryl nitriles has been reported. This protocol allows alpha-diaryl- and alpha-triaryl nitriles to be accessed in good to excellent yields and with a broad substrate scope, which could be further functionalized to give a versatile set of products. This is the first example wherein tert-butyl isocyanide has been used as a cyanide source for the 1,6-conjugate addition.

Oxone promoted dehydrogenative Povarov cyclization of N-aryl glycine derivatives: an approach towards quinoline fused lactones and lactams - More, Devidas A.; Shinde, Ganesh H.; Shaikh, Aslam C.; Muthukrishnan, M. (RSC Advances, 2019)
Oxone promoted intramolecular dehydrogenative imino Diels-Alder reaction (Povarov cyclization) of alkyne tethered N-aryl glycine esters and amides has been explored, thus affording biologically significant quinoline fused lactones and lactams. The reaction is simple, scalable, and high yielding (up to 88%). The method was further extended to prepare biologically important luotonin-A analogues and the quinoline core of uncialamycin.